(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Severe anaemia is usually treated with red blood cell (RBC) transfusion and in some cases moderate anaemia also requires transfusion. Traditionally one unit of red blood cells is transfused to increase the hemoglobin (Hb) level by 1 gm/dl, although no consensus guideline is available in our country. This study was done to see how much hemoglobin level was increased after transfusion of one unit of red blood cells in cancer patients with anaemia in our people. During the period of July 2012 to December 2012, 160 patients were studied in the Department of Transfusion Medicine of National Institute of Cancer Research and Hospital (NICRH), Mohakhali, Dhaka. All patients were aged >18 years of both sexes having a haemoglobin level of <10 gm/dl, and had no transfusion of platelets, plasma or colloid within 24 hours of red cells transfusion or with active bleeding or drain loss. The average increment of haemoglobin level was 0.74 gm/dl (0.74±0.11) gm/dl for each unit of red blood cells transfusion. This rise of haemoglobin level was different from the traditional calculation which was statistically significant (p<0.01). The traditional calculation for correction of anaemia by red blood cell transfusion is not suitable for the people of our country. JCMCTA 2014 ; 25 (2) : 21-25